Palangka Raya Police Collaborative Governance Strategy In Control Of Illegal Racing And Motorbike Gang Activities - Alpiani; Ditta Islammiyatul Khotimah; Nurlaila; Ahmad Syahrul Hendrawan; Angel Safitri; Pambajeng Luluh Dyah Pangestu; Imanuel Jaya (International journal of technology and education research, 2026)
The increasing phenomenon of illegal racing and motorcycle gang activity in Palangka Raya City has become a public security issue that cannot be addressed solely through law enforcement. This study aims to analyze the collaborative governance strategy implemented by the Palangka Raya Police in controlling illegal racing and motorcycle gang activity through the Pentahelix approach. The study used a descriptive qualitative method. The study population included stakeholders involved in controlling illegal racing, while informants were selected purposively, consisting of police personnel, local government, academics, community leaders, and residents. Data were collected through in-depth interviews, observations, and documentation studies. Data analysis was conducted qualitatively interactively using the Collaborative Governance and Pentahelix frameworks. The results show that the Palangka Raya Police implement preventive, repressive, and educational strategies supported by collaboration between the government, educational institutions, the community, the media, and the business world. Coordination, information exchange, and the utilization of shared resources contribute to suppressing illegal racing activities and increasing community participation. The study concludes that Pentahelix-based collaborative governance can strengthen the effectiveness and sustainability of illegal racing control through the integration of law enforcement, social supervision, education, and the provision of legal alternative facilities.